Growth differentiation factor 9:bone morphogenetic protein 15 heterodimers are potent regulators of ovarian functions - Peng, Jia (National Academy of Sciences, 2013)
The TGF-β superfamily is the largest family of secreted proteins in mammals, and members of the TGF-β family are involved in most developmental and physiological processes. Growth differentiation factor 9 (GDF9) and bone morphogenetic protein 15 (BMP15), oocyte-secreted paralogs of the TGF-β superfamily, have been shown genetically to control ovarian physiology. Although previous studies found that GDF9 and BMP15 homodimers can modulate ovarian pathways in vitro, the functional species-specific significance of GDF9:BMP15 heterodimers remained unresolved. Therefore, we engineered and produced purified recombinant mouse and human GDF9 and BMP15 homodimers and GDF9:BMP15 heterodimers to compare their molecular characteristics and physiological functions. In mouse granulosa cell and cumulus cell expansion assays, mouse GDF9 and human BMP15 homodimers can up-regulate cumulus expansion-related genes (Ptx3, Has2, and Ptgs2) and promote cumulus expansion in vitro, whereas mouse BMP15 and human GDF9 homodimers are essentially inactive. However, we discovered that mouse GDF9:BMP15 heterodimer is ∼10- to 30-fold more biopotent than mouse GDF9 homodimer, and human GDF9:BMP15 heterodimer is ∼1,000- to 3,000-fold more bioactive than human BMP15 homodimer. We also demonstrate that the heterodimers require the kinase activities of ALK4/5/7 and BMPR2 to activate SMAD2/3 but unexpectedly need ALK6 as a coreceptor in the signaling complex in granulosa cells. Our findings that GDF9:BMP15 heterodimers are the most bioactive ligands in mice and humans compared with homodimers explain many puzzling genetic and physiological data generated during the last two decades and have important implications for improving female fertility in mammals.